Acceleration Analysis of 3-DOF Planar Parallel Manipulators by Means of Screw Theory - Zarkandi, Soheil (Journal of Mechanical Engineering, 2016)
This paper deals with the second order kinematics of three degree-of-freedom (DOF) planar parallel manipulators. The simple and compact expressions are derived for both the inverse and forward acceleration analyses using screw theory. Moreover, as an example, a 3-DOF planar parallel manipulator is introduced and its kinematics is analyzed using the proposed method.